Study of the post operative outcome in orthopeadic management in cases of high HBA1c diabetic patients-a case series - Mahajan, Neetin P.; Chaudhari, Kunal; Talukder, Pritam; Pande, Kartik; Dadhaniya, Ravikumar (International Journal of Research in Medical Sciences, 2022)
Elderly diabetic patients are at risk of poor fracture healing in post-traumatic fracture seven due to trivial low energy falls and chronic pathological bone involvement. Glycated haemoglobins are haemoglobins with an attached sugar moiety. HbA1c is the predominant fraction of HbA1 and gives an estimate of the blood sugar levels of an individual over the last three months. Here we present a case series of 3 elderly patients who came to us with post traumatic fractures or chronic bone pathologies and very high HBA1C values (>10%) who required operative orthopaedics management. The injuries were adequately managed with splintage and operative procedures after proper control of the patients’ blood sugars levels. Postoperatively mobilization was challenging. Orthopaedic chronic bone pathologies and post traumatic limb fractures with uncontrolled sugar and very high HBa1c are very difficult to treat. Postoperatively patients are at a very high risk of infection, poor suture healing, risk of repeat fracture, osteoporosis, etc which often results into functional outcome being hampered. Proper counselling by operating surgeon, physiotherapy and postoperative rehabilitation with the help of relatives and assisting devices with strict preoperative and post operative sugar control provides good outcome. In cases of trauma in old age, one should always thoroughly examine and screen for comorbidities such as hypertension and diabetes using reliable markers such as HBa1c levels. So that early appropriate treatment and mobilization can be done with good functional outcome.